Combating Malnutrition : Time to Act - Gillespie, Stuart; McLachlan, Milla; Shrimpton, Roger (Washington, DC: World Bank and UNICEF, 2013)
Nutrition has been sidelined for too long. Reducing malnutrition is central to reducing poverty. Malnutrition is implicated in half of all child deaths, and causes much illness and cognitive underdevelopment. As the growing evidence demonstrates, fetal and young children malnutrition, threatens survival, growth, and development in childhood, and, it increases the risk of chronic diseases in later life. The Millennium Development Goals cannot be reached without significant efforts to eliminate malnutrition. The book looks at ways to combat malnutrition, by positioning nutrition directly on the poverty and human development policy agenda, to ensure large-scale nutrition actions, and develop capacity to address malnutrition. It provides key findings on the nutritional status, and the broad consensus on what needs to be done, through the analyses of the evolution of policy narratives, country case studies, and workshops, that are behind the headlines, in order to show how policy changes in nutrition happen, what influences these processes, and, what lessons can be learned for the future.